The Role of Muhammad Obid Sindi's Work "Al-Mawahibu-L-Latifa" in the Science of Hadith - Anvarov, Elyorbek (Jurnal Pendidikan Islam, 2025)
This study explores the significance of Muhammad Obid Sindi’s seminal work al-Mawahib al-Latifa in the development of hadith sciences. The book represents a unique scholarly effort in analyzing hadith transmission chains (isnad), narrators’ reliability (jarh wa ta’dil), rare linguistic expressions, and jurisprudential interpretations (fiqh al-hadith). Unlike many predecessors, Sindi systematically categorized hadith, clarified textual complexities, and strengthened weak narrations with corroborative evidences, thereby elevating their status for jurisprudential use. His approach integrated the disciplines of hadith methodology, Arabic grammar, and Islamic jurisprudence, reflecting an advanced interdisciplinary scholarship. This paper argues that Sindi’s contributions extended beyond commentary, serving as a bridge between traditional hadith sciences and their application in legal and theological contexts. Ultimately, al-Mawahib al-Latifa emerges as a vital reference for understanding the authenticity, interpretation, and application of prophetic traditions within the broader Islamic scholarly heritage.